Crystallization and mechanical properties of metallocene made 1-butene-pentene and 1-butene-hexene isotactic copolymers. (5th December 2018) - Tarallo, Oreste; Ruiz de Ballesteros, Odda; Bellissimo, Annalisa; Scoti, Miriam; Malafronte, Anna; Auriemma, Finizia; De Rosa, Claudio
Abstract: The structure and the mechanical properties of metallocene-made butene-pentene (iPBC5) and butene-hexene (iPBC6) isotactic copolymers are studied. The effect of the presence of pentene and hexene units on the crystallization behavior and the mechanical properties of isotactic polybutene (iPB) is analyzed. All iPBC5 copolymers crystallize from the melt in form II of iPB, which transforms into form I by aging at room temperature. On the contrary, in iPBC6 copolymers the presence of hexene units stabilizes the form II and, for hexene concentrations higher than 11 mol%, prevents the transformation of form II into form I at room temperature. Both iPBC5 and iPBC6 copolymers show mechanical behavior of highly flexible and ductile materials with enhanced ductility compared to iPB, with values of stress at yielding and of Young's modulus that decrease with increasing comonomer content. In all the iPBC5 copolymers, form II crystallized from the melt transforms into form I by stretching, whereas in iPBC6 copolymers form II is stabilized and the transformation of form II into form I by stretching is completely inhibited at high hexene concentrations. Graphical abstract: Highlights: High pentene concentration in butene-pentene copolymers favors cold-crystallization of form I. Hexene co-units stabilize form II in isotactic copolymers with butene. In pentene/butene copolymer stretching induces form II to form I transition. Hexene co-units inhibit form II to form I transition by effect of stretching. Pentene or hexene comonomeric units enhance ductility of isotactic polybutene.